2011
DOI: 10.1111/j.1558-5646.2011.01308.x
|View full text |Cite
|
Sign up to set email alerts
|

Pumping Ions: Rapid Parallel Evolution of Ionic Regulation Following Habitat Invasions

Abstract: Marine to freshwater colonizations constitute among the most dramatic evolutionary transitions in the history of life. This study examined evolution of ionic regulation following saline-to-freshwater transitions in an invasive species. In recent years, the copepod Eurytemora affinis has invaded freshwater habitats multiple times independently. We found parallel evolutionary shifts in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
219
5
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(251 citation statements)
references
References 71 publications
16
219
5
11
Order By: Relevance
“…Little is known about the osmoregulation of copepods, and marine copepods are considered osmoconformers (Mauchline, 1998). However, the calanoid copepod Eurytemora affinis has the capability to osmoregulate via the ion‐transport enzymes V‐type H + ‐ATPase and Na + /K + ‐ ATPase, an ability that allowed it to colonize freshwater from marine environments (Lee, Kiergaard, Gelembiuk, Eads, & Posavi, 2011). Our findings with C. glacialis lend additional support to the osmoregulatory capacity of marine copepods, possibly via sodium:proton antiporters.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the osmoregulation of copepods, and marine copepods are considered osmoconformers (Mauchline, 1998). However, the calanoid copepod Eurytemora affinis has the capability to osmoregulate via the ion‐transport enzymes V‐type H + ‐ATPase and Na + /K + ‐ ATPase, an ability that allowed it to colonize freshwater from marine environments (Lee, Kiergaard, Gelembiuk, Eads, & Posavi, 2011). Our findings with C. glacialis lend additional support to the osmoregulatory capacity of marine copepods, possibly via sodium:proton antiporters.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lee et al (2011) found an expansion of plasticity after a marine to freshwater invasion by the copepod Eurytemora affinis. This habitat shift of E. affinis occurred only 150-300 generations ago, such that insufficient time may have accumulated for assimilation of plasticity.…”
Section: Research Articlementioning
confidence: 99%
“…We found that executing laboratory selection in response to crude oil was comparatively more difficult relative to the ease to which laboratory populations of E. affinis could respond to selection in response to salinity or temperature stress (Ketzner & Bradley, 1982; Lee et al., 2007, 2011). The selection experiments in this study used similar approaches as prior studies, with similar starting population size (hundreds of copepods).…”
Section: Discussionmentioning
confidence: 99%